The Swedish system for compensation of patient injuries - Johansson, Henry (Informa Healthcare, 2010)
Since 1975 Sweden has had a patient insurance system to compensate patients for health-related injuries. The system was initially based on a voluntary patient insurance solution, but in 1997 it was replaced by the Patient Insurance Act. The current Act covers both physical and mental injuries. Although about 9,000–10,000 cases are processed in Sweden annually, compensation is paid in barely half of these cases. In the Swedish patient injury claim processing system, the Patient Claims Panel is the authority that plays an important role in ensuring fair and consistent application of the Act.